Pharmacokinetics, Pharmacodynamics and Tolerability of a Potent, Non-peptidic, GP IIb/IIIa Receptor Antagonist following Multiple Oral Administrations of a Prodrug Form - Refino, Canio J.; Modi, Nishit B.; Bullens, Sherron; Pater, Cheryl; Lipari, Michael T.; Robarge, Kirk; Blackburn, Brent; Beresini, Maureen; Weller, Thomas; Steiner, Beat; Bunting, Stuart (Thrombosis and Haemostasis, 1998)
Ro 44-3888 is a potent and selective antagonist of GP IIb/IIIa. Following IV administration to rhesus monkeys, the (mean ± SD.) clear ance, volume of distribution and terminal half-life of Ro 44-3888 were 4.4 ± 1.8 ml/min/kg, 0.8 ± 0.4 l/kg and 2.5 ± 0.8 h respectively. Oral administration of Ro 48-3657 (1 mg/kg), a doubly protected prodrug form, produced peak concentrations of Ro 44-3888 (152 ± 51 ng/ml), 4.2 ± 2.2 h after dosing. Terminal half-life and estimated bioavailabil ity were 5.1 ± 1.6 h and 33 ± 6% respectively. No effect on blood pressure, heart rate or platelet counts were seen. Adenosine diphosohate (ADP) induced platelet aggregation (PA) and cutaneous bleeding times (CBT) were determined prior to and after the last of 8 daily oral administrations of Ro 48-3657 (0.25 or 0.5 mg/kg) to eight rhesus monkeys. Peak and trough plasma concentrations were proportional to dose and steady state was achieved after the second administration. Inhibition of PA and prolongation of CBT were concentration dependent. The ex vivo IC50 (82 nM) for ADP-mediated PA correlated with a value (58 nM) determined in vitro. The CBT response curve was displaced to the right of the PA curve. CBT was prolonged to ≥25 min when levels of Ro 44-3888 exceeded 190 nM and PA was >90% inhibited. Therefore, in rhesus monkeys, Ro 48-3657 is reproducibly absorbed and converted to its active form, is well tolerated, and has a concentration-dependent effect on PA and CBT. These properties make Ro 48-3657 an attractive candidate for evaluation in patients at high risk for arterial thrombosis.